2013
DOI: 10.1007/s12603-013-0034-7
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional status according to the Mini Nutritional Assessment (MNA®) and frailty in community dwelling older persons: A close relationship

Abstract: These results underline the close association between frailty syndrome and nutritional status in older persons. A profound understanding of the interdependency of these two geriatric concepts will represent the basis for successful treatment strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
91
3
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 157 publications
(108 citation statements)
references
References 29 publications
5
91
3
5
Order By: Relevance
“…Our result may be compared with a previous Spanish study which found a significant association between the five frailty criteria and the categories of MNA, and that the largest proportion of frail subjects were at risk of malnutrition (15) . Additionally, 90 % of malnourished elderly patients were either pre-frail or frail, and about 36 % or 57 % of the frail people were malnourished or at risk of malnutrition (14,66) . These authors also found that the prevalence of malnutrition was six times higher in frail older adults compared with robust individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Our result may be compared with a previous Spanish study which found a significant association between the five frailty criteria and the categories of MNA, and that the largest proportion of frail subjects were at risk of malnutrition (15) . Additionally, 90 % of malnourished elderly patients were either pre-frail or frail, and about 36 % or 57 % of the frail people were malnourished or at risk of malnutrition (14,66) . These authors also found that the prevalence of malnutrition was six times higher in frail older adults compared with robust individuals.…”
Section: Discussionmentioning
confidence: 99%
“…The MiniNutritional Assessment MNA) and its short form have been well validated for use in older populations to identify those at risk (44)(45)(46)(47)(48)(49). However, it needs to be recognized that the MNA also is likely to identify persons at risk for frailty (50). Other screening tools that are commonly used are the Nutrition Risk Screening 2002 and the Malnutrition Universal Screening Tool (MUST) (51,52).…”
Section: Figure 2 Mechanisms By Which Dysphagia Causes Undernutritionmentioning
confidence: 99%
“…However, it should be recognized that all frail persons are not malnourished (41)(42)(43)(44). When frailty and malnutrition co-exist they are highly predictive of mortality in functionally impaired persons (45).…”
mentioning
confidence: 99%
“…There is evidence that diet quality in later life may influence the development of frailty (49)(50)(51)(52). Adherence to the Mediterranean diet appears to be particularly protective against developing frailty (53)(54)(55)(56).…”
mentioning
confidence: 99%